2021
DOI: 10.3390/biology10020116
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pirin, an Oxidative Stress Sensor Protein, in Epithelial Carcinogenesis

Abstract: Pirin is an oxidative stress (OS) sensor belonging to the functionally diverse cupin superfamily of proteins. Pirin is a suggested quercetinase and transcriptional activator of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway. Its biological role in cancer development remains a novel area of study. This review presents accumulating evidence on the contribution of Pirin in epithelial cancers, involved signaling pathways, and as a suggested therapeutic target. Finally, we propos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 98 publications
(134 reference statements)
0
23
0
Order By: Relevance
“…A number of studies have documented the tumour-promoting roles of pirin in human cervical, lung, oral, and skin cancers, and have been recently reviewed [ 29 ]. However, the status of pirin in colorectal cancer has not been documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have documented the tumour-promoting roles of pirin in human cervical, lung, oral, and skin cancers, and have been recently reviewed [ 29 ]. However, the status of pirin in colorectal cancer has not been documented.…”
Section: Discussionmentioning
confidence: 99%
“…Our functional studies show that pirin depletion does not affect the viability or migration of DLD1 colorectal cancer cells, and thus the functional significance of pirin overexpression in colorectal cancer requires further investigation. In this context, it is notable that a recent bioinformatic analysis has shown that pirin is functionally associated with six proteins, including Nck-associated protein 1 (NCKAP1) and cytoplasmic protein (NCK1) [ 29 ]. Both NCKAP1 and NCK1 have been implicated in facilitating cell invasion in breast cancer [ 30 , 31 ], suggesting that one of the functions of pirin overexpression is to promote cancer cell invasion, and that the invasion-promoting activity of pirin could be mediated through its functional interactions with NCKAP1 and/or NCK1.…”
Section: Discussionmentioning
confidence: 99%
“…This protein is predominantly expressed in human liver, heart, kidneys, and muscles while low levels of expression are observed in brain and lungs (Wendler et al 1997 ; Pang et al 2004 ). Human pirin has been implicated in skin, breast, lung, head and neck, gastrointestinal, cervical cancers (Perez-Dominguez et al 2021 ) and tumors of epithelial tissues, hematopoietic and neurological systems (Yoshikawa et al 2004 ; Licciulli et al 2010a ; Jungk et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic cigarette smoking causes increased oxidative stress, which up-regulates expression of pirin and it has been implicated in bronchial epithelial cell apoptosis (Hübner et al 2009 ; Chorley et al 2012 ). Pirin is an oxidative stress sensor (Perez-Dominguez et al 2021 ) and ferric conformation of this protein facilitates binding of NF-κB p65 to DNA (Liu et al 2013 ). Although elevated activation of p65 is observed in chronic inflammation (Giridharan and Srinivasan 2018 ), canonical NF-κB pathway mediated by p65/p50 heterodimer is critically important for innate immunity and inflammatory responses (Oeckinghaus and Ghosh 2009 ; Liu et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation